Women prime ministers and COVID-19: Within-case examinations of New Zealand and Iceland - Tyner, Katie; Jalalzai, Farida (Politics & Policy, 2022)
As COVID-19 cases and deaths mounted globally in the spring of 2020, the news media presented a narrative that women heads of government were more successful at handling the pandemic, sparking a scholarly debate. We take an in-depth look at two of the headline women-led cases (New Zealand and Iceland) to identify critical junctures and crucial actors in the policy-making process. Our research questions are as follows: What main factors comprised the executive decision-making process and approach to COVID-19 management in New Zealand and Iceland, and to what extent do these factors intersect with prevailing gender stereotypes of feminine leadership? We conducted elite interviews with senior politicians and civil servants in New Zealand and Iceland and found that consensus-oriented governance, honest and frequent communication with the public, agile and adaptive institutions, deference to scientific advice, collective and decisive action, and policies guided by empathy and humility have proved critical in these cases, and that many of these factors are associated with stereotypically feminine leadership traits. Published version